Determinants of foreign direct investment inflows to Malaysia / Nur Fathihah Mohd Yusof and Tay Bee Hoong - Mohd Yusof, Nur Fathihah; Tay, Bee Hoong (2013)
This paper aims to investigate the important factors that influence foreign direct investment (FDI) inflows to Malaysia. A multiple linear regression analyses by using Ordinary Least Squares (OLS) method are used in order to find the best fit model to explain variations in FDI inflows. Six (6) independent variables identified for this study are export, import, inflation, population, current account balance and quasi money. This study involves annual data from year 1981 until 2011. The finding of this study indicates that only import can be used to explain the variation in FDI inflows. Import is significant towards the study at 10% level of significance. Import is an important indicator because it reflects the amount of Foreign Direct Investment made from other countries into Malaysia. Malaysian government should focus more on the import activities in order to enhance the amount of FDI inflows and thus, it will also increase the government revenues. Other combinations of independent variables fail to satisfy all of the statistical tools examined in this study thus appear to be insignificant in explaining FDI inflows to Malaysia.